PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER), TOTAL ASSET TURNOVER (TAT), RETURN ON ASSET (ROA), DAN PRICE EARNING RATIO (PER) TERHADAP RETURN SAHAM (Pada Perusahaan Retail yang Terdaftar di Bursa Efek Indonesia 2010-2014) - Kurniatun, Maya; Nugraha, Hari Susanta; Saryadi, Saryadi (Jurnal Ilmu Administrasi Bisnis, 2015)
Investors have to make the right decision to invest. Investors can analyze the condition of the company by looking at its financial performance. This research was conducted to examine the effect of variable of Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turnover (TAT), Return on Assets (ROA), and Price Earning Ratio (PER) of the Stock Return, either partially or simultaneously at retail companies listed in Indonesia Stock Exchange in 2010-2014.This research is an explanatory research with 22 companies as population and the number of sample that examined after passed the purposive sampling phase is 12 companies. The results of regression analysis shows that the variable of Total Asset Turnover (TAT), Return on Assets (ROA), and Price Earning Ratio (PER) partially give significant effect on stock returns, while the variable of Current Ratio (CR), Debt to Equity Ratio (DER ) partially give no effect on stock returns. These five variables used in this study (CR, DER, TAT, ROA, and PER) simultaneously affect 58% to the stock return.Investors need to be cautious in making investments, the Current Ratio (CR) and Debt to Equity Ratio (DER) that are too high tends to pose a risk. Whereas the Total Asset Turnover (TAT), Return on Assets (ROA), and Price Earning Ratio (PER) may be used by investors as a parameter to measure the performance of the company to predict stock returns.